AWAKE BRAIN SURGERY IN A PATIENT WITH GLIOBLASTOMA - Adramanova, Dona; Stolevski, Vlado; Abbas, Nebil; Strezoska, Marija; Dimovski, Aleksandar; Jakimoska Dimkovska, Marina (Department of Anaesthesia and Reanimation, Faculty of Medicine, “Ss. Cyril and Methodius” University in Skopje, R.N.Macedonia, 2024)
The awake craniotomy, as a surgical procedure, facilitates maximal resection of brain tumors with minimal or no damage to eloquent brain areas. Conscious sedation and asleep-awake-asleep techniques are two anesthetic techniques employed. During the awake phase, the patient should be alert and cooperative, with adequate analgesia as an essential component of the anesthetic management while neurological testing is performed. Ensuring airway patency, proper oxygenation and ventilation, avoidance of hypoxia and hypercarbia, and maintaining stable systemic and cerebral hemodynamics are crucial. We present a case of a right-handed 56-years-old man with speech difficulties manifested as fluent dysphasia and magnetic resonance findings of intra-axial supratentorial left-sided temporoparietal lesions. The patient was scheduled for awake brain surgery according to the affected eloquent language brain area of the dominant hemisphere. Asleep-awake-asleep anesthetic technique was utilized. Short-acting sedative agents propofol and dexmedetomidine were used, along with remifentanil and fentanyl as analgesics. After awakening, neurological testing of sensory, motor and cognitive functions was performed, revealing no new neurological deficits and achieving maximally safe microsurgical tumor resection with stable hemodynamics and no respiratory or intracranial adverse events. With histopathological findings of glioblastoma (WHO Grade IV), chemotherapy and radiotherapy followed the surgery. The available literature demonstrates the importance of the extent of tumor resection for improved outcomes and survival benefits in glioma surgery, with maximal resection without excising functional brain tissue, being the primary goal of awake brain surgery.